Distributed Modifier Adaptation using a Coordinator and Measured Interconnection Variables. Issue 1 (July 2017) - Milosavljevic, Predrag; Schneider, René; Faulwasser, Timm; Bonvin, Dominique
Abstract: We propose a distributed real-time optimization scheme for structurally uncertain systems consisting of multiple interconnected subsystems. In particular, we investigate a novel distributed variant of modifier adaptation that exploits a coordinator and knowledge of interconnection model. This way, each subsystem can compute its optimal inputs using only local information in terms of model, gradients and measurements. A coordinator ensures that the local optimal inputs computed by each subsystem are consistent with the interconnection model. In addition to ensuring confidentiality of local data, the scheme also guarantees plant optimality upon convergence. The analysis is illustrated via a simulation example.